HISTOPATHOLOGICAL STUDY OF PROSTATIC LESIONS AND ASSESSEMENT WITH AGNOR INDEX - K.SUBATHRA; N.SANGEETHA (International Journal of Pharma and Bio Sciences, 2014)
Interpretation of prostatic biopsies has been a continuous problem for practicing pathologist. This current study aims at the analysis of histopathological features of various non neoplastic and neoplastic lesions of the prostate including the grading of malignant lesions and evaluation of role of AgNOR index in different benign, premalignant and malignant lesions of prostate. One hundred and eight transurethral resection of prostate specimens were studied with haematoxylin and eosin and AgNOR staining. Benign prostatic hyperplasia was the most common lesion affecting the prostate in elderly. High grade prostatic intra epithelial neoplasia had strong association with prostatic carcinoma. Among the malignant lesions of the prostate, primary prostatic adenocarcinoma was the commonest. According to Gleason Grading system higher grades were more commonly observed as the predominant pattern. Mean AgNOR counts were higher in malignant lesions when compared with the benign lesions.